PENGARUH PENGETAHUAN DAN MOTIVASI KERJA DOKTER SPESIALIS TERHADAP PENGISIAN REKAM MEDIS RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN - Anthonyus Anthonyus (Elisabeth Health Jurnal, 2019)
Medical Record is a collection of data and information on patients related to administration, medical clinical processes and medical support, quality management and outcome of those processes, which are documented and stored systematically and safely to be used by parties Entitled and concerned.. Aim: The purpose of this study was to analyze the influence of the knowledge and motivation of the specialist's work on the filling of the medical record in the hospital ward of Santa Elisabeth Hospital. Method: Type of research using explanatory research with associative approach. Population is all the specialist doctors who become Doctors in Patient Responsibility inpatient at Santa Elisabeth Hospital as many as 50 people, while the sample of research as many as 50 people. Data collection was done by giving questionnaires and observation sheet of medical record. Analysis of data with Chi Square and multiple logistic regression. Results: The results showed that: 1) The knowledge of specialist physicians influenced the filling of hospitalized medical records at Santa Elisabeth Hospital Medan. This is indicated by the value of p = 0.030, the value of exp (B) 6,837. 2) Working motivation of specialist doctors influential on filling in medical records inpatient Hospital Santa Elisabeth Medan. This is indicated by the value of p = 0.005, the value of exp (B) 6,635. 3). Conclusion: There is a positive and significant influence between the knowledge and motivation of the specialist's work on the filling of the hospitalization records of Santa Elisabeth Hospital in Medan..